2019
DOI: 10.1111/tbed.13123
|View full text |Cite
|
Sign up to set email alerts
|

Identification of six novel capsular polysaccharide loci ( NCL ) from Streptococcus suis multidrug resistant non‐typeable strains and the pathogenic characteristic of strains carrying new NCL s

Abstract: Streptococcus suis is a major swine pathogen and an important zoonotic agent worldwide. At least nine serotypes can infect human so far. Although 29 serotypes (1–19, 21, 23–25, 27–31 and 1/2) strains are considered as authentic S. suis, a novel variant serotype Chz and strains carrying 20 novel capsular polysaccharide loci (NCL) have been identified recently. However, information about pathogenic and antimicrobial resistance characteristics of strains carrying NCLs is still unavailable. In this study, we ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…In addition to the "classical" described serotypes, a novel variant (serotype Chz) and strains carrying 26 novel capsular polysaccharide loci (NCL1-26) have been identified recently [28][29][30][31][32]. These findings expand the views of the genetic diversity of S. suis cps loci.…”
Section: Figurementioning
confidence: 81%
“…In addition to the "classical" described serotypes, a novel variant (serotype Chz) and strains carrying 26 novel capsular polysaccharide loci (NCL1-26) have been identified recently [28][29][30][31][32]. These findings expand the views of the genetic diversity of S. suis cps loci.…”
Section: Figurementioning
confidence: 81%
“…Most virulence-associated genes preferentially present in highly pathogenic S. suis serotype 2 strains were absent from all serotype 7 genomes. Previous studies also reported that these virulence markers studied in S. suis serotype 2 strains were not suitable as virulence markers for S. suis non-serotype 2 strains [ 3 , 12 , 44 ]. Thus, S. suis serotype 7 virulent strains may utilize a different pathogenesis strategy.…”
Section: Discussionmentioning
confidence: 99%
“…The serotype distribution can also change with time in the same territory. A new very virulent serotype, the Chz serotype, responsible for meningitis in pigs, seems to have emerged in recent years, and 20 new cps loci (NCL) have been identified in non-typeable isolates [ 12 , 13 ]. Strains of S. suis can also be classified into three groups according to their pathotypes: (i) a “non-clinical” group for strains originating from the upper respiratory tract microbiota that do not trigger symptoms or cause the death of its host, (ii) a “respiratory” or “possibly opportunistic” group of strains generally sampled in lungs from clinically sick animals or from clinically healthy animals in farms that have suffered from outbreaks of S. suis , and (iii) a “pathogenic” or “systemic” group of strains obtained from samples of blood nervous and/or articular systems and identified as the causes of infection [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%